Effects of β-caryophyllene and Murraya paniculata essential oil in the murine hepatoma cells and in the bacteria and fungi 24-h time-kill curve studies - Maria Cipriano Selestino Neta; Catia Vittorazzi; Aline Cristina Guimarães; João Damasceno Lopes Martins; Marcio Fronza; Denise Coutinho Endringer; Rodrigo Scherer (Taylor & Francis Group, 2017)
Context: Orange Jessamine [Murraya paniculata L. (Rutaceae)] has been used worldwide in folk medicine as an anti-inflammatory, antibiotic and analgesic. Objective: The objective of this study is to investigate the in vitro antioxidant, cytotoxic, antibacterial and antifungal activity and the time-kill curve studies of orange jessamine essential oil and β-caryophyllene, as well as the chemical composition of the essential oil. Material and methods: The cytotoxic activity of M. paniculata and β-caryophyllene (7.8-500 μg/mL) was evaluated using the MTT assay on normal fibroblasts and hepatoma cells. The minimal inhibitory concentration and time-kill curves (24 h) were evaluated against those of Staphylococcus aureus, Escherichia coli, Salmonella typhimurium, Enterococcus faecallis, Aspergillus (niger, fumigates and parasiticum) and F. solani by the broth microdilution method. The antioxidant activity was measured by the DPPH and ABTS assays. Chemical composition was evaluated by GC/MS analyses. Results: GC/MS analyses identified 13 compounds, with β-caryophyllene as the major compound. The oil exhibited moderate antibacterial activity (MIC <1.0 mg/mL) and strong antifungal activity. Time-kill curve studies showed that either the essential oil or β-caryophyllene presented rapid bacterial killing (4 h for S. aureus) and fungicidal effect (2-4 h for F. solani); however, both displayed weak free radical scavenger capacity. The cytotoxic activity exhibited a prominent selective effect against hepatoma cancer cells (IC50 value =63.7 μg/mL) compared with normal fibroblasts (IC50 value =195.0 μg/mL), whereas the β-caryophyllene showed low cytotoxicity. Discussion and conclusion: The experimental data suggest that the activities of M. paniculata essential oil are due to the synergistic action among its components.